Work Life balance major key driver for Employee Engagement - et. al., Kshama Pathak, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Work Life balance has become a predominant issue in any workplace in today’s world. Human Resource Management have been immensely researching on work-life balance to motivate employee performance and increase employee engagement in the workplace. This study helps us to see that work-life balance activities at workplace not just has effects on an employee’s life but also improves the overall performance of an employee towards his work. These activities have an effect to significantly improve the employee morale, retain employees in the organization, reduce absenteeism and improve the organization performance which is very important in these difficult economic times. This helps not just the millennial employees but also single mothers who are trying to balance their career or new couples struggling to manage career and their personal life or even when employers struggle to retain their employees, work life balance activities offer a great help to the employees and the employers.